THE VALUES OF LEARNING IN THE DANGEROUS MINDS MOVIE BY JOHN N SMITH - Amiruddin, Amiruddin; Nurjannah, Salma (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
The research was conducted to know: how are the educational values on the learning process contained in the film Dangerous Minds. The use of research methods that are seen from the type of research that uses a qualitative study/approach is to observe and direct the film. As for analyzing the authors using a qualitative descriptive analysis technique, that describes the values contained in the film. The results of this research show that there are learning values in Film Dangerous Minds, which are various theories of learning namely, theories of learning behaviorism, learning Theory of cognitivism, learning theory of constructivism, learning theory of humanism. Then several methods of learning are methods of learning questions and answers, methods of learning recitation (giving assignments), methods of learning lectures, learning methods of discussion.